The Development of Portable Power Generator by Using Thermoelectric Generator for Hiking Purpose - Razali, Muhammad Insannulkamil; Mohd Zin, Rosnah (Evolution in Electrical and Electronic Engineering, 2021)
The development of this project is to generate electricity from heat using the thermoelectric generator. This project is made for hikers. The power generator works as a tool that generate electricity and can be recharged using heat from a fire. This power generator comes with a sensor, which works to produce electricity when there is a different temperature detected. It can be used to charge a phone, power bank and others. The problem is while hiking when hikers running out of battery for their essential electronic devices. Thermoelectric generators will be used as a primary source to convert heat energy into electrical energy and become an input to the direct current (DC) buck converter. The DC buck converter will step down the voltage and boosts the current from the input to the load output. The universal serial bus (USB) module is used for charging electronic devices. The capability of this device to charge the electronic devices has been tested and it can charge about 10 percent in 30 minutes.